Innovation of Natural and Social Science E-Module Based on MERDEKA Flow Integrated with Tri Nga to Improve Critical Thinking Dimension of Elementary School Students - Isnani Fauziah Saptiyanti; Pardimin; Ana Fitrotun Nisa (Jurnal Ilmiah Sekolah Dasar, 2024)
In order to realize the achievement of the critical thinking dimension, innovation in learning resources is needed, one of which is in the form of e-module. This study aims to produce e-module with characteristics based on MERDEKA flow and integrated with Tri Nga which feasible and effective to improve critical thinking dimension of elementary school students. This study uses research and development research method using ADDIE model (analysis, design, development, implementation, evaluation). Data collection techniques in this study were carried out using observation, interview, questionnaire and documentation techniques. Data analysis techniques in this study were carried out using qualitative and quantitative data techniques. The subjects in this study involved three experts, 9 teachers of grade V of elementary school, 2 principals, and 86 students of grade V of elementary school, of which 29 students were the subjects of limited trial and 57 students were the subjects of extensive trial. The results of this study indicate that generated electronic module with characteristics based on MERDEKA flow with consist of stages: starting from students themselves, concept exploration, collaboration space, contextual demonstration, elaboration of understanding, connection between materials and real action. Electronic module also integrated with Tri Nga which consist of stage ngerti, ngrasa, and nglakoni. Results of validity test obtained an average of 3,77 with a percentage of 94,6% with very feasible criteria. The effectiveness of improving critical thinking is also included in High category.  So, it can be concluded that an e-module based on MERDEKA flow integrated with Tri Nga was produced to improve critical thinking dimension of elementary school students.